On Fiscal Policy and Budget Deficits - Philip Arestis; Malcolm Sawyer (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2004)
A major argument used against the use of fiscal policy comes from the view that there are automatic forces within an economic system to ensure high levels of demand. This paper argues that the case for fiscal policy in general rests on the proposition that there are no such market forces that ensure high levels of demand. There is, thus, a need for macroeconomic policy to perform this task. The argument against fiscal policy to the effect that it does not raise the level of economic activity, does not apply when this view of fiscal policy is adopted.
Keywords: E62; 330